2019
DOI: 10.28991/cej-2019-03091425
|View full text |Cite
|
Sign up to set email alerts
|

Study on Retrofitting of RC Column Using Ferrocement Full and Strip Wrapping

Abstract: Ferrocement is one of the cement-based composites used for retrofitting and rehabilitation among many applications. Ferrocement is one of the reinforced concrete form with lightweight and thin composite with durability and environmental resistant that strengthen the conventional RC columns to increase its strength and serviceability. This paper examines the performance of the ferrocement wrapping in RC columns experimentally with numerical simulation using ANSYS19. Totally sixteen number of RC column of size 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…In addition, masonry is a material that is vulnerable and easy to experience failure (brittle), so strengthening the building wall is highly recommended by using the proper retrofitting method [18,19].…”
Section: Inter Story Driftmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, masonry is a material that is vulnerable and easy to experience failure (brittle), so strengthening the building wall is highly recommended by using the proper retrofitting method [18,19].…”
Section: Inter Story Driftmentioning
confidence: 99%
“…The ferrocement layer is mortar containing woven wire mesh that was installed on a masonry wall (ferrocement layer retrofitting method). From the previous studies, it was found that retrofitting the building wall using a ferrocement layer increases the capacity of the wall [18][19][20][21]. An analysis was carried out using the ETABS v.18 programs for modeling and analysis of the building retrofitted using the ferrocement layer.…”
Section: Retrofitting Building Wall Using Ferrocement Layermentioning
confidence: 99%
“…Many research studies have been performed on environmental preservation and sustainable development by efficiently utilizing various waste residues in bricks' production. These wastes include bottom ash, fly ash, blast furnace slag, saw-dust, furniture waste, crumb rubber, tea waste, rice husk ash, sugarcane bagasse ash, cotton waste, and limestone [6,7].…”
Section: Introductionmentioning
confidence: 99%